Internationalisation Of Chinese Higher Education: Application Of Knowledge Management To Analysis Of Tsinghua University - Kuang, Ping; Marshall, Ian (Journal of Knowledge Management Practice, 2010)
Tsinghua University is one of China's most influential universities. This paper uses it as a case study of the reasons as to why it stands out in China in the process of internationalisation of higher education, by means of a knowledge management (KM) social-technical theory model. A literature study of this model, mainly based on the work of Lee and Choi (2003), can offer a holistic approach in describing organisational culture, structure, people and technical support as well as the relationship between each element and knowledge creation and internationalisation of higher education.
Keywords: Knowledge management; Internationalisation of higher education; Tsinghua University; Case study